Determinants of E-Logistic Customer Satisfaction: A Mediating Role of Information and Communication Technology (ICT) - Waseem-Ul- Hameed; Shahid Nadeem; Muhammad Azeem; Ahmad Ibrahim Aljumah; Raji Abdulwasiu Adeyemi (International Journal of Supply Chain Management, 2018)
In the recent decade, with the increase in e-logistic services, the problem of e-logistic customer satisfaction is raised. E-logistic services spread so rapidly worldwide which overlook the significant segment of customer satisfaction. Therefore, the prime objective of the current research study is to develop a comprehensive framework for e-logistics customer satisfaction. Various studies highlighted the area of e-logistic customer satisfaction, however, in a rare case, literature formally documented the problem of e-logistic customer satisfaction. Hence, less attention has been paid to the aspect of customer satisfaction in e-logistic. To address this gap, four hypotheses are proposed concerning the relationship of e-payment, e-traceability, website design with information communication technology (ICT) and e-logistic customer satisfaction. By using the convenience sampling technique, 500 questionnaires were distributed among the e-logistic users. The results of the current study found that e-payment, e-traceability, and website design has a significant positive relationship with ICT and ICT has a significant positive relationship with e-logistic customer satisfaction. This study is contributing to the body of knowledge by developing a comprehensive framework to solve various e-logistic problems. Hence, the current study is helpful for e-logistic companies to mitigate e-logistic customer satisfaction problems.